Piezoelectric materials : applications in SHM, energy harvesting and bio-mechanics /: applications in SHM, energy harvesting and bio-mechanics. ([2017]) - Bhalla, Suresh; Kaur, Naveet; Talakokula, Visalakshi; Moharana, Sumedha
No abstract available